Awareness of green technology adoption by selected wood furniture industries in Peninsular Malaysia - Ambra Singh, Kaljeet Singh (2016)
The awareness of green technology is important to ensure proper adoption in an organization. In Malaysia, green technology refers to products, equipment, and systems used to conserve the natural environment and resources, which minimizes the negative impact of human activities. Green technology brings about tremendous environmental and financial benefits (cost saving) besides creating the organization’s environmental reputation. The government has provided various incentives to encourage green technology uptake by industries in Malaysia. This study looks into the level of awareness on green technology adoption by selected wood furniture industry in Peninsular Malaysia. The goal is to gauge current understanding and practices related to green technology amongst the target group. The extent of green skills development in this industry was also examined. To achieve this, survey questionnaire that consists of various constructs to determine awareness level of green technology adoption was prepared and provided to selected green companies located in Peninsular Malaysia during Malaysian International Furniture Fair (MIFF 2015) and International Greentech & Eco Products Exhibition & Conference Malaysia (IGEM 2015). Results from direct engagement with the survey respondents show that understanding of green technology definition amongst the target group need improvement. Top management plays a crucial part to ensure proper guideline and policy exist in the organization for green technology adoption. Although there are initiatives and ventures into green technology adoption, skill development in the industry also need to be addressed as this ensures that there are proper talent to execute green agenda set in the organization. Additionally, emphasis on incentive uptake needs to be made as this provide financial assistance provided by the government to organizations.